2009
DOI: 10.1037/a0016437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neonatal handling on playfulness by means of reversal of the desire to play in rats (Rattus norvegicus).

Abstract: In the present study the authors sought to establish whether the range of effects of neonatal handling stimulation (H), that is, brief daily periods of infant isolation, could be extended to the domain of social motivation. With this aim, the authors studied the innate motivation to engage in rough-and-tumble play (R&T) in adolescent rats (Rattus norvegicus) by means of a reversal design, in which half of the rats were first housed in isolation (Days 1-3), and then in company (Days 4-6), while the other half f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
(45 reference statements)
5
15
1
1
Order By: Relevance
“…As shown in Aguilar et al (2009), early handling had modest effects on dorsal contacts, with H rats outperforming their NH counterparts only the first day of testing in Parts 2 and 5, an effect that dissipated thereafter as a result of gradual diminution of this behavior in H rats. This pattern of results in conjunction with the increments in pin frequency observed with time of isolation appears to indicate that H rats tended to make dorsal contacts more frequently than NH controls when not engaged vigorously in reciprocal pinning.…”
Section: Does Early Handling Modify the Mechanisms Of Play Motivation?mentioning
confidence: 88%
See 3 more Smart Citations
“…As shown in Aguilar et al (2009), early handling had modest effects on dorsal contacts, with H rats outperforming their NH counterparts only the first day of testing in Parts 2 and 5, an effect that dissipated thereafter as a result of gradual diminution of this behavior in H rats. This pattern of results in conjunction with the increments in pin frequency observed with time of isolation appears to indicate that H rats tended to make dorsal contacts more frequently than NH controls when not engaged vigorously in reciprocal pinning.…”
Section: Does Early Handling Modify the Mechanisms Of Play Motivation?mentioning
confidence: 88%
“…The treatment of early handling was the same as in Aguilar et al (2002Aguilar et al ( , 2009, performed twice daily (morning and evening) from postnatal Day 1 to Day 18. Briefly, it consisted of placing the pups individually in plastic cages (42 × 26 × 18 cm) for a total period of 10 min, each pup being gently handled by the experimenter from the head to the tail with his forefinger for 5 s (one stroke per second).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in both cases, the pups were subjected to high-licking mothers because handling induces a burst in licking behavior (de Azevedo et al, 2010). A previous study (Aguilar, Caramés, & Espinet, 2009) showed that neonatal handling may increase the frequency of pinning behavior, provided that the animals were previously socially isolated. In that specific situation of social deprivation, handled rats showed increased social play behavior instead of the decrease described herein.…”
Section: Discussionmentioning
confidence: 99%